Spontaneous Coronary Artery Dissection and a Family History of Aortic Dissection: A Genetic Association Study - Lucy McGrath‐Cadell; Stephanie Hesselson; Ingrid Tarr; Emma M. Rath; Michael Troup; Yunkai Gao; Keerat Junday; Monique Bax; Siiri E. Iismaa; Nicholas Collins; David W. M. Muller; Jason C. Kovacic; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Spontaneous coronary artery dissection (SCAD) is an increasingly recognized cause of acute coronary syndrome or sudden cardiac death, primarily affecting relatively young women (median age, 51 years) without typical cardiovascular risk factors. SCAD has a genetic component, with genome‐wide association studies identifying multiple risk loci. Thoracic aortic dissection (type A) shares some genetic overlap with SCAD, suggesting potential common predispositions. Methods We performed genetic screening or whole‐genome sequencing of 17 patients with SCAD (94% women) with a first‐ or second‐degree relative (89% men) affected by aortic dissection (AD). We assessed rare variants in candidate genes and genome‐wide using the American College of Medical Genetics and Genomics criteria. Polygenic risk scores were calculated to assess genetic risk for SCAD, fibromuscular dysplasia, AD, and abdominal aortic aneurysm in patients with SCAD, relatives with AD, and controls. Results Whole‐genome sequencing identified pathogenic or likely pathogenic variants in SMAD3, CBS, and COL3A1 in 3 SCAD cases. Additionally, 4 variants of uncertain significance were found in candidate genes. Polygenic risk scores for SCAD were significantly associated with increased odds of SCAD in probands versus controls (odds ratio, 1.79 [95% CI, 1.08–2.99]; P=0.024). Conclusions Our study supports a complex genetic landscape underlying SCAD, implicating rare monogenic pathogenic variants and polygenic risk. We identified pathogenic variants in patients with SCAD with a family history of AD, highlighting potential genetic links between these vascular disorders. The findings underscore the importance of genetic screening in patients with SCAD with a history of AD to identify individuals at risk and guide preventive strategies.